PENGETAHUAN TRADISIONAL PETANI DALAM PENANGANAN PASCA PANEN CENGKEH DI DESA WAODE BURI KECAMATAN KULISUSU UTARA KABUPATEN BUTON UTARA - Mardin Mardin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
The objective of this study is to ascertain the traditional knowledge possessed by farmers in Waode Buri Village, North Kulisusu District, North Buton Regency, concerning post-harvest handling of clove plants. The informants for this study were clove farmers residing in Waode Buri Village. The selection of informants was conducted in accordance with a set of predetermined criteria, culminating in a total of seven individuals who were deemed eligible for participation in the study. The data for this study was collected through a combination of methods, including observation, documentation, and in-depth interviews guided by a structured interview protocol. The present study concentrated on the knowledge that farmers possess regarding the post-harvest handling of clove plants. The collected data were then subjected to analysis using the qualitative analysis method proposed by Milles & Huberman, which includes data collection, data reduction, data presentation, and conclusion drawing/verification. The findings of the study suggest that farmers' comprehension of post-harvest management of cloves in Waode Buri Village demonstrates their awareness of the significance of sorting, drying, packaging, and storage processes in preserving clove quality prior to sale. In the post-harvest handling of cloves, farmers continue to utilize traditional methods that have been handed down through generations. However, challenges persist in the post-harvest handling process, including restricted access to market information and minimal utilization of contemporary technology.